Rethinking Indoor Environment Demand and Control in Hot Summer from a “Yin Summer-Heat” Perspective in Traditional Chinese Medicine - Siwei Xu; Jia Du; Bin Chen (Buildings)
Air conditioning is the most common and efficient measure against summer heat. However, overcooling issues exist widely in well-conditioned buildings, and the health risks and causes require further exploration. This study aims to rethink the indoor environment control and demand in hot summer from a novel perspective of yin summer-heat in traditional Chinese medicine. The core idea was to reflect health risks embodied in the indoor environment control that was oriented by the average comfort zone in air-conditioned buildings. Three research questions were explored, namely, indoor–outdoor environment features in hot summer, the heterogeneity of demands and behaviors, and relationships between personal attributes and lifestyles. Eleven field tests were conducted in residential buildings, together with experiments in an office building and three questionnaire surveys with 765 responses from 2020 to 2023 in China. Results showed that notable indoor–outdoor environment gaps appeared due to air conditioning. Yin summer-heat symptoms, such as a heavy feeling in the body, were reported by individuals of vulnerable constitutions even in neutral air-conditioned environments. In addition, Chinese medicine theories, including pathogenic factors, constitutions, and health preservation principles, worked well to interpret diverse environment perceptions, demands, and adaptive behaviors. These findings will add to the scientific basis of wellbeing in indoor environments.